Hazardous gases and fumes - Warren, Peter J. (Butterworth-Heinemann, 1997)
The substances dealt with in this book vary considerably in their properties, whether it be chemical, physical or physiological, and, as a consequence, in the risks they pose to health and safety and the conditions demanded of staff and workplaces which handle them. It is therefore important not only to be able to identify both the gases and fumes themselves, but the dangers which they pose and the consequent measures necessary to deal with those dangers, whether it be as a precautionary measure or in response to an incident. For these reasons the availability of the data contained in this book will be of interest to staff on sites where such substances are used as well as those who may need to react to an accident involving their use such as fire-fighters, doctors, nurses, paramedics, and other emergency response staff.
Includes index.
Keywords: Hazardous substances.; Gases, Asphyxiating and poisonous.; Industrial safety.; elektronické knihy; electronic books